Eksistensi Kawin Sumbong Masyarakat Baru Lempur Dalam Perspektif Hukum Islam - Edi, Zalman; Halim, Abdul; Yuliatin, Yuliatin (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2026)
This study aims to analyze the phenomenon of kawin sumbong in Desa Baru Lempur, Gunung Raya District, Kerinci Regency, focusing on its implementation, existence, and its review from the perspective of Islamic law. Although considered a violation of customary norms, this tradition is not intended to prevent marriage but to enforce moral responsibility and maintain social harmony. This research employs Spradley’s ethnographic approach using qualitative methods through participant observation, in-depth interviews, and documentation. Data were analyzed using the Miles and Huberman model, including data collection, reduction, display, and conclusion drawing until saturation was achieved. The findings reveal that kawin sumbong requires a customary fine in the form of one goat and the ulu nasi ritual as a symbolic act of atonement. After fulfilling the customary requirements, the marriage proceeds and the couple is socially accepted. Despite modernization, this tradition continues to exist. From an Islamic legal perspective, the practice does not invalidate the marriage because it does not contradict syariah provisions regarding permissible kinship. The customary fine functions as a moral symbol to preserve peace, prevent family conflict, and strengthen kinship ties.